Factors Influencing the Thai-owned Family Business’ Effectiveness: A Case of Vanachai Group - Chaipattanawanich, Vanich; Preudhikulpradab, Sirichai (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
This study is survey-based, using the structured questionnaire as the primary research instrument for data collection, analysis, and interpretation leading to a proposed recommendation for organization development. Research objectives: 1. to determine the factors influencing the effectiveness of a Thai-owned family business and the correlation among the independent variable, and 2. to propose recommendations for organizational development of the business based on the findings. The research site, population, and sample are a local Thai privately-owned company, full-time employees of 1,300 (N), and actual respondents of 348 (n) selected by simple random sampling and voluntary basis. The research findings showed that adaptability (Beta=.255, Sig<.000, Rank1), team collaboration (Beta=.239, Sig.<.000, Rank 2) and communication (Beta=.130, Sig<.022, Rank3) as the independent variables that significantly influenced the business’ effectiveness The proposed recommendations for organization development comprise individual, team, and organization levels.